Complex of test exercises: the key to success in children's sports - Pazdnikova, N. P.; Opletin, A. A.; Romanov, V. V.; Maksimova, A. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to create and demonstrate the efficacy of a set of assessment tasks for children, tailored to their developmental stage and aligned with their sensitive developmental period.